2008
DOI: 10.1017/s0263034608000256
|View full text |Cite
|
Sign up to set email alerts
|

External magnetic field effect on plume images and X-ray emission from a nanosecond laser produced plasma

Abstract: The plume images of the laser produced silver plasma in the absence and presence of 0.45 T transverse magnetic field has been investigated under vacuum ~10−4 torr and in air. An Nd:YAG laser (1.064 µm, 1.1 MW, 9 ns) with intensity ~1012 Wcm−2 was used to generate plasma. A CCD image capture system was used for plasma imaging to explore the plume. A magnetic probe was employed to measure the variation in internal magnetic field of plasma with as well as without 0.45 T external transverse magnetic field. The X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The plasma expansion dynamics was investigated by means of fast photography imaging. Fast photography and plasma spectroscopy have been widely used to gain information about physical quantities that characterize the plasma and to detect the presence of atomic and/or molecular species in the plasma (Thareja & Sharma, 2006;Trusso et al, 2005;Schade et al, 2006;Rafique et al, 2008;Hafeez et al, 2008). In this study, data on physical quantities such as the initial expansion velocity, the mass, the temperature, and the emission intensity as recorded from time resolved fast photography imaging of the expanding plume were used to obtain realistic parameters for the mixed-propagation model.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma expansion dynamics was investigated by means of fast photography imaging. Fast photography and plasma spectroscopy have been widely used to gain information about physical quantities that characterize the plasma and to detect the presence of atomic and/or molecular species in the plasma (Thareja & Sharma, 2006;Trusso et al, 2005;Schade et al, 2006;Rafique et al, 2008;Hafeez et al, 2008). In this study, data on physical quantities such as the initial expansion velocity, the mass, the temperature, and the emission intensity as recorded from time resolved fast photography imaging of the expanding plume were used to obtain realistic parameters for the mixed-propagation model.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the expansion of plasma plume and diffusion of plasma species are decelerated by the applied magnetic field. According to Rafique et al 29 the lifetime of plasma plume is increased in the presence of magnetic field. Khaleeq et al 30 reported that the density of laser induced electrons increased in the presence of magnetic field.…”
Section: A Ion Energy and Dose Measurementsmentioning
confidence: 99%
“…The reason for the improved uniformity and the particle size in case of the film deposited under the influence of external magnetic field is attributed to the enhancement in the forward peaking [17] of Zn, Mn, Zr and Fe ions. The plume is more confined with larger densities under the influence of external magnetic field [13]. In the absence of external magnetic field, the average particle size of the thin film of sample Y, i.e.…”
Section: Sem Analysismentioning
confidence: 99%
“…In our previous work, it was reported that there is a change in the plume propagation properties under the influence of an external magnetic field [13], which has significant effect on the growth of thin films [14].…”
Section: Introductionmentioning
confidence: 99%